Arabidopsis PROTEASOME REGULATOR1 is required for auxin-mediated suppression of proteasome activity and regulates auxin signalling - Bao-Jun Yang (Nature Portfolio, 2016)
Plant responses to auxin require proteasome-mediated degradation of Aux/IAA transcriptional repressor proteins. Here, Yang et al. show that auxin suppresses proteasome activity in a manner dependent on the proteasome regulator PTRE1 and propose a mechanism for fine tuning Aux/IAA homoeostasis.